“Identification of a Rare Splice Site Mutation in a Palestinian Family With West Syndrome” - Dweik, Hamza (Palestine Polytechnic University, Bethlehem University)
West Syndrome is a convulsive disorder consists of a triad of a unique seizure type (spasms), hypsarrhythmia, and developmental arrest or regression. It begins in infancy, mostly between 4 and 6 months of life. Its incidence worldwide is approximately 2-5 per 10,000 live births; however, in Palestine there is no statistical data available. The syndrome is classified according to etiology into symptomatic, cryptogenic and idiopathic. WS has many causes, and their mechanisms are still unclear. It is a genetically heterogeneous condition, and the number of the discovered genes are increasing. In this research the DNA of a Palestinian family were sequenced by next generation exome sequencing analysis. Validation of genotype to phenotype segregation was done using classical Sanger Sequencing method, also a 100 healthy individuals were analyzed to identify the carrier frequency among the healthy Palestinian population. The results of exome sequencing revealed a substitution mutation (G>A) at the 5`splice donor site of the ARFGEF2 gene in the locus chr20:47,592,737 (c.1985+ 1G>A). The substitution activated cryptic splice site at the previous exon (exon 14) that leads to deletion of 44 base pairs of that exon as was shown by sanger method. DNA sanger sequencing results indicates that this ARFGEF2 c.1985+ 1G>A mutation segregates perfectly with the phenotypes in the family under an autosomal recessive mode of inheritance. Using 100 Palestinian healthy controls, we could not find this mutation either in homozygous or heterozygous state.
CD 29374- NO. of pages 63
Keywords: Science in bitechnology